KERJASAMA GURU DENGAN ORANG TUA UNTUK MENUMBUHKAN KEDISIPLINAN PESERTA DIDIK KELAS V A UPTD SD N. 1 ALOR KECIL KECAMATAN ALOR BARAT LAUT KABUPATEN ALORTAHUN PELAJARAN 2024/2025 - Noho, Mahmud Abdullah; Ahmad, Santri Putriwati; Amsidi, Mukmin (STKIP Muhammadiyah Kalabahi, 2025)
In creating a disciplined character in students, the teacher's efforts alone are not enough, so there needs to be cooperation from other parties concerned such as parents and the surrounding environment. Collaboration between teachers and parents to foster student discipline at UPTD SD Negeri Alor Kecil can run well, if there is joint synergy between teachers and parents to improve student discipline, so that there are no longer differences in perception or differences of thought between both in educating children to be disciplined. The form of collaboration carried out by UPTD SD Negeri Alor Kecil is to foster student discipline by establishing an association of parents and teachers, socializing the rules that must be obeyed by all students, accepting criticism and suggestions from parents, using the facilities and infrastructure available at the school. and make visits to students' parents' homes if necessary. This research uses a qualitative research method with a case study type of research. Determining the subjects of this research used a purposive sampling technique. The research subjects in this study were the homeroom teacher, class V A students and parents. The data collection techniques used were non-participant observation, in-depth interviews, and documentation. The data analysis techniques used in research are data reduction, data presentation and conclusion drawing. Data validity techniques by combining various data collection techniques and existing data sources. This research uses research techniques and sources. The results of the research show that the process of collaboration between teachers and parents has gone well, but there are still several shortcomings that must be addressed and completed so that the form of collaboration between teachers and schools runs much better, judging from Thomas Lickona's theory which says there are 20 ways To build collaboration between teachers and parents, UPTD SD Negeri Alor Kecil is still implementing 10 ways to build collaboration between teachers and parents and of the ten ways that have been implemented there are several ways that have not worked perfectly and still need improvement, especially the aspect of making family homework.